Avaliação das atividades anti-toxoplásmica, antioxidante e antiinflamatória dos monoterpenos timol (lippia sidoides) e estragol (croton zenhtneri) - Oliveira, Claudio Bruno Silva de (2012)
Toxoplasmosis, a benign disease in normal healthy individuals, can have serious effects in pregnant women and immunocompromised patients. It is a parasitic disease caused by Toxoplasma gondii (Tg), an obligatory intracellular protozoan. The prophylactic and therapeutic arsenal against this parasite is very restricted. Thus, there is an ongoing search for novel drugs and therapeutic strategies. A promising alternative is a rational approach using medicinal plants. This study aimed to standardize methodologies for assessing the toxicological, antiproliferative, antioxidant, antiinflammatory and anti-Toxoplasma effects of Estragole and Thymol compounds isolated from species of plants (Lippia sidoides and Croton zenhtneri) commonly used in the Cariri region of Ceara State, Brazil. First we evaluated in vivo toxicity and conducted a pathological analysis of mice livers. In vivo antiinflammatory activity was assessed using air pouch and paw edema methods. Cytotoxicity assays were performed and antiproliferative, antioxidant and nitric oxide production analyzed. Anti-Toxoplasma activity was evaluated in a congenital experimental model with varying stages of maternal infection using the ME-49 strain and a non- congenital model by using ME-49 and RH strains. The results suggest low to moderate toxicity for both compounds. Thymol was more toxic in vivo and in vitro, having greater pathological repercussion than Estragole. The compounds were inactive for antiproliferative activity. Thymol showed better antioxidant activity, while Estragole stimulated nitric oxide production in macrophages. Both showed significant antiinflammatory activity. In non-congenital Tg infection, both compounds were active only against the ME49 strain. In congenital infection, Estragole (oral route) improved the newborn weight of infected mothers compared with untreated controls. Subcutaneous administration of the two compounds increased the weight of offspring born to infected mothers compared with untreated controls. We concluded that Estragole and Thymol exhibit important biological and anti-Toxoplasma activities. Further studies are needed to elucidate the mechanism of action of these compounds and other possible activities not investigated in the present study